PENGARUH POLA ASUH ORANG TUA DAN MOTIVASI TERHADAP PRESTASI BELAJAR SISWA KELAS XI IPS SMA NEGERI 5 PALU - Samintang Samintang (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) IAIN Palu, 2020)
This study aimed to obtain information about (1) Is there any influence parenting parents on student achievement class XI IPS SMAN 5 Palu. (2) Is there any influence of motivation on student achievement class XI IPS SMAN 5 Palu. The method used is descriptive quantitative method. The population of as many as 133 students at SMAN 5 Palu. Total sample as many as 57 people using Proportional sampling techniques. Data collection techniques using a questionnaire Likert scale models, observation, interview and documentation. The data analysis technique that is the first data reduction, data presentation, and draw conclusions. The results showed that: First, there is the influence of Parenting Students (X1) to the learning achievement (Y), parenting applied in SMA Negeri 5 Hammers Class XI IPS namely Democratic Parenting With the percentage rate of 35,73%. In this case of course the child's success in school with high academic achievement can not be separated from parenting parents, the family is the first social group where children can interact. Family influence in the formation and development of personality is very large. Second, From the analysis it is known that the implications of the results of motivation on learning achievement has significant impact on the increase in student motivation. Motivation of students at SMAN 5 Hammers Class XI IPS can already be said to be good with a percentage of 63.44%. Motivation resulting in students not be separated from the teachers themselves. A student learning because it is driven by the power of mental form of desires, concerns, wishes, or ideals, mental strength and can be classified as low and high depending on the efforts of teachers to encourage students and reward so that students feel able to be better.